2012
DOI: 10.1007/s00383-012-3206-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro CO2-induced ROS production impairs cell cycle in SH-SY5Y neuroblastoma cells

Abstract: In vitro-simulated pneumoperitoneum environment with CO(2) induces oxidative stress and cell DNA damage, leading to p53 up-regulation involved in cell-cycle arrest of neuroblastoma cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…DNA damage was evaluated by using a single‐cell gel electrophoresis technique as previously described (Montalto et al, ). Briefly, after treatment, harvested cells were embedded in a thin agarose gel (1% low melting point) on a microscope slide.…”
Section: Methodsmentioning
confidence: 99%
“…DNA damage was evaluated by using a single‐cell gel electrophoresis technique as previously described (Montalto et al, ). Briefly, after treatment, harvested cells were embedded in a thin agarose gel (1% low melting point) on a microscope slide.…”
Section: Methodsmentioning
confidence: 99%
“…Our results showed that in vitro simulated CO 2 pneumoperitoneum environment induces oxidative stress, leading to DNA damage followed by a significant attenuation of cell proliferation mediated by p53 activation. 6 We also reported that CO 2 -induced hypoxic condition exerts cytotoxic effects on NB cells by eliciting mitochondrial apoptotic pathway. 7 It has been well established that cell response to hypoxic stress is mediated by HIFs.…”
Section: Discussionmentioning
confidence: 75%
“…5 The presence of HIF-1α and HIF-2α has been revealed in NB specimens; however, the expression of both proteins did not fully correlate and was dependent on the microenvironment. 18 Although HIF-1 and HIF-2 share common targets involved in many pathways, such as angiogenesis, differentiation, stem cells maintenance, apoptosis, and invasion, 6 it has been previously reported that HIF-1α is associated with a favorable outcome, whereas HIF-2α is implicated in promoting an aggressive NB phenotype correlating with an unfavorable clinical outcome. 19 Our results showed that the exposure of SH-SY5Y NB cells to 15 mm Hg CO 2 (100%) for 4 hours caused an increase in the transcript levels of HIF-1α, which returned to basal levels after 24 hours of incubation in standard condition; in contrast, no changes were observed in the mRNA levels of HIF-2α, suggesting that an acute hypoxic stimulus can be associated with a favorable outcome in our NB cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular level, CO 2 -induces changes in pH and may alter neuronal excitability by altering extracellular adenosine and ATP concentrations (Xu, Uh et al, 2011). CO 2 insufflation-induces oxidative stress and has a toxic effect on neuroblastoma cells leading to DNA damage (Montalto, Currò et al, 2013). In E. coli, CO 2 was seen to exacerbate the toxicity of ROS in a dose-dependent manner (Ezraty, Ducret et al, 2011).…”
Section: Discussionmentioning
confidence: 99%